Development of antidepressant drugs through targeting a4ß2-nicotinic acetylcholine receptors - Zhang, H.; Gunosewoyo, Hendra; Yan, F.; Tang, J.; Yu, L. (2016)
© Springer Science+Business Media New York 2016. Nicotinic acetylcholine receptors (nAChRs) represent a family of ligand-gated ion channels that are ubiquitously distributed in the central and peripheral nervous systems. There is a considerable line of evidence both from clinical and preclinical studies supporting the notion that antagonism or partial agonism of these receptors, particularly the a4ß2-containing subunits, could lead to antidepressant-like effects in vivo. In this chapter, an overview of the fundamental neuropharmacology of a4ß2-nAChRs underpinning its association with depression is covered, including the original cholinergic hypothesis of depression proposed by Janowsky in the 1970s. The primary section highlights important structural classes of compounds that have been reported to mediate antidepressant-like effects through targeting of a4ß2-nAChRs with an emphasis on their potency, selectivity, pharmacokinetics, and drug-likeness. The pyridyl ether ligands represent the most promising scaffold for selective targeting of a4ß2-nAChRs and their antidepressant- like effects have been confirmed in animal behavioral studies. Recent advances in the field, including the use of imaging technologies for depression, are also discussed, highlighting the evolution of structural classes that have been developed as useful positron emission tomography (PET) ligands in imaging nicotinic receptors.